Guidelines for Integration of Systematic Reviews using Primary Studies - Botelho, Ricardo Vieira; Oliveira, Matheus Fernandes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
Objectives Due to the growing number of systematic reviews published and the need to update the existing revisions, the Agency for Healthcare Research and Quality (AHRQ) – Evidence-based Practice Centers (EPC) published in 2008 a preliminary guide to integrate primary data education to data from systematic reviews already published. This study is a translation effort of the American agency's guidelines to provide subsidies for revisions in our midst.Methods A study group with experts in systematic review was gathered to identify any methodological requirements that need clarification and guidance to revision developers that used existing reviews. In addition, they identified and consulted experienced researchers to provide guidance on conducting systematic reviews: Key informants (KI).Results No evidence was found in the literature for the driving advice based on the integration of existing systematic reviews and primary assays. Recommendations were based on expert opinion.Conclusion The literature lacks guidelines for integration of systematic reviews and primary studies.
Keywords: systematic reviews; primary studies; clinical research